Shear strength anisotropy of natural London Clay - Nishimura,S; Minh,NA; Jardine,RJ (2011)
The paper reports the shear strength anisotropy of the natural, highly overconsolidated, London Clay from Heathrow Terminal 5 as established by comprehensive hollow cylinder apparatus (HCA) testing. Multiple high-quality block samples from 5.2 m and 10.5 m below ground level provided samples for suites of undrained stress-path shear tests performed after consolidation to effective stress states similar to those estimated in situ. The direction of the major principal stress axis, α (or of the principal stress increment, αdσ), and relative magnitude of the intermediate principal stress, b = (σ2 - σ3)/ (σ1 - σ3), were chosen as the controlled stress-related variables and their influence on the peak shear strength was investigated. Strong shear strength anisotropy was proven, and a potential effect of the parameter b was also detected. With b = 0.5, for example, a minimum was noted in peak q/p′ at around α = 45 67°, and the maximum value, which was larger by some 40%, developed at α = 0°. A limited set of data obtained with larger test specimens suggested a possibility that loading with α = 90° could also lead to relatively low shear strength. The pre-failure pore water pressure development reflected anisotropy of the deformation characteristics at smaller strains and contributed to the total-stress undrained shear strength anisotropy. Regarding the influence of b, the Mohr Coulomb failure line passing through the data for b = 0 or 1 provided a lower bound of all the data for a given value of α. The investigation of anisotropy was extended to deeper horizons of the stratum through profiling tests involving triaxial extension and simple shear conditions. Although the results confirmed the general patterns of anisotropy observed at 5.2 and 10.5 m below ground level, the degree